2021
DOI: 10.1123/jsr.2019-0469
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Training on Dynamic Neuromuscular Control in Fencers: A Clinical Trial

Abstract: Context: Fencing is a sport of agility, with a higher incidence of lower-limb injuries, of which the ankle sprain is the most prevalent. Injury prevention is very important to improve performance and decrease the withdrawal time of athletes. Proprioceptive training programs can be added to the training of athletes, since, in addition to easy application and low cost, proprioception has the function of stabilizing the ankle joint to prevent injuries. Objective: To verify the influence of a 12-week proprioceptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The current results were similar to those of de Vasconcelos and colleagues in that there was no observed difference in reach distance between the dominant and non-dominant lower extremities. 15 Conversely, Guan and colleagues identified a side-to-side difference in the posterolateral direction, but their statistically significant findings were derived from combined data from fencers and Tae Kwon Do athletes. 14 One possible explanation for the discrepant findings could be due to the chosen study population.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The current results were similar to those of de Vasconcelos and colleagues in that there was no observed difference in reach distance between the dominant and non-dominant lower extremities. 15 Conversely, Guan and colleagues identified a side-to-side difference in the posterolateral direction, but their statistically significant findings were derived from combined data from fencers and Tae Kwon Do athletes. 14 One possible explanation for the discrepant findings could be due to the chosen study population.…”
Section: Discussionmentioning
confidence: 97%
“…Two recent studies have used the SEBT, from which the YBT is derived, to evaluate dynamic balance performance in child and club-level fencers. 14,15 Their authors reported conflicting findings regarding the presence of dynamic balance asymmetry in their participants. The current results were similar to those of de Vasconcelos and colleagues in that there was no observed difference in reach distance between the dominant and non-dominant lower extremities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations